2004
DOI: 10.1021/la048979f
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in the c(4×2) Reconstruction of Hexadecanethiol on Au(111) Revealed by Grazing Incidence X-ray Diffraction

Abstract: The c(4 x 2) structure of C16H33SH alkanethiol monolayers self-assembled on Au(111) has been studied by grazing incidence X-ray diffraction. This structure coexists on the surface with the (radical3x radical3)R30 degrees phase. The structural refinement of the c(4 x 2) phase has been accomplished by omitting the fractional order reflections common to both structures. The surface unit cell consists of four symmetry-independent molecules with atomic displacements related by couples, such that only two nonequival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 26 publications
(43 reference statements)
6
93
0
Order By: Relevance
“…There are two relatively recent SXRD studies, one of the (√3x√3)R30° phase of dodecylthiolate [86], the other of the (2√3x3)rect. phase of hexadecylthiolate [46]. As remarked earlier, the long chain thiolates at high coverage invariably lead to a coexistence of the (√3x√3)R30°…”
Section: Specifically Morikawa Et Almentioning
confidence: 57%
See 2 more Smart Citations
“…There are two relatively recent SXRD studies, one of the (√3x√3)R30° phase of dodecylthiolate [86], the other of the (2√3x3)rect. phase of hexadecylthiolate [46]. As remarked earlier, the long chain thiolates at high coverage invariably lead to a coexistence of the (√3x√3)R30°…”
Section: Specifically Morikawa Et Almentioning
confidence: 57%
“…A more recent SXRD investigation of the (2√3x3)rect. phase of hexadecylthiolate (n=16) [46], however, based on a very much larger data set than that which appears to have been used in the original 1994 study, concluded that the two inequivalent S headgroup adsorption sites were the fcc and hcp hollow sites. This investigation sought to minimise the problem of the coexistence of the (√3x√3)R30° and (2√3x3)rect.…”
Section: Overviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Evidence against the dimer model was presented by scanning tunneling microscopy [42] and by electron spectroscopy experiments [43]; in the latter, thiolate dimers were found only at temperatures above 375K. In recent He and X-ray diffraction experiments it was concluded that in the (4 2) c × superstructure alkyl-thiolate molecules adsorb as monomers on the Au(111) surface [44,45].…”
Section: Structuresmentioning
confidence: 99%
“…A persisting controversy surrounds the precise adsorption site of the sulfur headgroup on the Au(111) surface. Time of flight scattering and GXRD studies emphasize adsorption at (fcc and hcp) hollow sites [111,112], where the sulfur head-group binds to three Au surface atoms, while photoelectron diffraction (PED) and normal incidence x-ray standing wave (NIXSW) studies prefer on-top adsorption, where sulfur binds to one Au atom [113,114] . Computational studies offer a third possibility.…”
Section: Sam Induced Surface Reconstructionsmentioning
confidence: 99%